(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The authors’ research investigated human metacommunications from the perspective of how these signals could be interpreted and used as risk indicators during customs controls. Modern customs technology uses risk indicators to create risk profiles, separate risk groups, and assign risk levels. One element of the research is identifying other researchers’ published results in scientific studies of human metacommunication and the lessons we could learn from these previous studies. Methodology: The authors chose to start their study by conducting a scientometric analysis using a database of publications with global coverage and high academic prestige. They decided on the Elsevier Scopus repository from several possible database options and used the keyword search method. They analysed the published data set between 1971 and 2021 using Elsevier’s SciVal analysis tool. The statistical analysis, a measure of scientific performance, focuses on the metadata of publications and provides the opportunity to identify in-depth correlations between these papers. Findings: A statistical analysis of the core population of n = 2278 publications and the exploration of metadata of reduced records between 1997 and 2021 allowed us to understand deeper correlations between records of n = 2101. The study on a sufficiently large number of individuals demonstrated the multiand interdisciplinary nature of the topic and the growing scientific interest in its research. Value: The study has identified core elements of the theme, its links and the scientific discipline fields identified by the publications investigated. The analysis includes an overview of the authors, institutions and countries that have published the most, the new scientific value provided by the publications, and the leading scientific journals for scientific discourse. On this basis, the authors suggest further research directions, particularly for researchers in law enforcement sciences.